2015
DOI: 10.1007/s00520-015-2694-9
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in patients with ovarian cancer and bowel obstruction

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…A systematic review of 868 patients with MBO showed that surgery was able to palliate obstructive symptoms (32–100%), enable resumption of a modified diet (45–75%), and facilitate successful patient discharge to home (34–87%) [ 54 ]. Similar results were found in another study examining treatment outcome for MBO under a multidisciplinary care model [ 10 ]. Compared to patients who received medical treatment, the surgical group had longer median survival ( p =0.025), shorter hospitalization ( p =0.02), more effective pain reduction ( p =0.001), higher number of chemotherapy lines ( p =0.02), and lower reobstruction rate ( p =0.02) [ 10 ].…”
Section: Surgical Intervention For Mbosupporting
confidence: 89%
See 3 more Smart Citations
“…A systematic review of 868 patients with MBO showed that surgery was able to palliate obstructive symptoms (32–100%), enable resumption of a modified diet (45–75%), and facilitate successful patient discharge to home (34–87%) [ 54 ]. Similar results were found in another study examining treatment outcome for MBO under a multidisciplinary care model [ 10 ]. Compared to patients who received medical treatment, the surgical group had longer median survival ( p =0.025), shorter hospitalization ( p =0.02), more effective pain reduction ( p =0.001), higher number of chemotherapy lines ( p =0.02), and lower reobstruction rate ( p =0.02) [ 10 ].…”
Section: Surgical Intervention For Mbosupporting
confidence: 89%
“…Similar results were found in another study examining treatment outcome for MBO under a multidisciplinary care model [ 10 ]. Compared to patients who received medical treatment, the surgical group had longer median survival ( p =0.025), shorter hospitalization ( p =0.02), more effective pain reduction ( p =0.001), higher number of chemotherapy lines ( p =0.02), and lower reobstruction rate ( p =0.02) [ 10 ]. A prospective outcome analysis was performed on 26 patients with ovarian cancer who had undergone palliative procedures, including bowel diversion surgery ( n =8), intestinal bypass/resection ( n =6), and endoscopic procedures ( n =12) [ 9 ].…”
Section: Surgical Intervention For Mbosupporting
confidence: 89%
See 2 more Smart Citations
“…3 Although cachexia has long been acknowledged as a cardinal symptom of advanced ovarian cancer, 16 evidence on its actual prevalence are scarce, estimated somewhere in the lower to middle 2-digit range (36%Y40%), and there is hardly any information on its prevalence at the onset of disease. 27,28 The cohort of patients for whom body composition data at time of first diagnosis was available is listed separately. Brackets indicate percentage (%) if not indicated otherwise.…”
Section: Discussionmentioning
confidence: 99%